Trends in Physical Activity Among US Adults With Heart Failure, 2007-2016. Issue 5 (September 2021) - Ye, Fan; Yale, Steven; Zheng, Yi; Hu, Hui; Zhou, Li; Fanning, Jason; Yeboah, Joseph; Brubaker, Peter; Bertoni, Alain G.
Abstract : Purpose: Lack of physical activity (PA) is an important risk for heart failure (HF). The objective of this study was to examine PA trends in HF and non-HF participants from a nationally representative sample of US adults from 2007 to 2016. Methods: Work-related/recreational activities (min/wk) were calculated on the basis of the reported frequency, intensity, and duration, respectively. Multivariable analyses were performed using National Health and Nutrition Examination Survey data. Results: Among 28 824 participants, younger (aged 18-64 yr) HF participants reported less PA time than non-HF groups, especially vigorous PA. Differences were found to be smaller in older (≥ 65 yr) participants. Overall, the percentage of younger participants who met PA guidelines was significantly lower in the HF individuals in work-related PA and total PA from 2007 to 2016 than in the non-HF participants (OR = 0.55: 95% CI, 0.39-0.59 for total PA, 0.45, 0.28-0.75 for vigorous work-related PA, and 0.68, 0.47-0.97 for moderate work-related PA, respectively). In older participants, only when considering total PA, the prevalence of meeting PA guidelines was significantly different between HF and non-HF groups (0.78, 0.62-0.98). Conclusions: Self-reported PA, especially vigorous activities, is much lower in older HF participants. However, the disparity in meeting PA guidelines between those with HF and without HF is remarkable in younger individuals. Future research should focus on better understanding the psychological and physical barriers to engaging in PA among HF patients. Abstract : Supplemental Digital Content is Available in the Text.Self-reported physical activity, especially vigorous activities, is much lower in older (65 yr of age and older) heart failure participants. However, the disparity in meeting physical activity guidelines between those with heart failure and without heart failure is remarkable in younger individuals (aged 18-64 yr).